Prévalence Et Diversité De Salmonella En Afrique : Analyse Qualitative Et Quantitative - Alio Sanda Abdelkader; Samna Soumana Oumarou; Inoussa Maman Maârouhi; Diallo Bouli Ali; Bakasso Yacoubou (European Scientific Journal, ESJ, 2017)
International trade, new agricultural, animal production and food practices have facilitated the spread and transmission of food-borne pathogens; including Salmonella. Salmonella is a ubiquitous bacterium responsible for a variety of diseases in humans, animals. It has a large diversity and contains more than 2579 serotypes. However, very little work describing the diversity, structure and populations dynamics of Salmonella in different hosts is available in Niger. In order to describe the general context of Salmonella diversity in Africa, an analysis of the available literature on this subject was carried out. A total of 131 publications were identified. From those publications, twenty five (25) were eligible. The LOGIT estimation model was used for serotype analysis to standardize the distribution of data and minimize sample sizes. It appears from our analysis that the prevalence of Salmonella is high regardless of the host and host germ. The major serotypes found in humans in Africa are S. Typhimurium, S. Enteritidis and S. Typhi. In poultry, the predominant serotype is S. Hadar on the other side S. Typhimurium predominates in North Africa. Thus, the results of these review analyzes constitute one of the steps in the process of understanding trends in the distribution of Salmonella in Africa. These results are presented as an outline of the implementation of a successful 251 model for the continuation of our studies on the diversity of Salmonella in Niger.